Strengthening the skills of fifth-grade elementary school students in mastering fractional numbers through a realistic mathematics approach - Rochaendi, Endi; Ariyani, Yusinta Dwi; Sari, Indah Perdana; Kurniati, Hanik; Arifin, Ahmad Syamsul (Universitas Kanjuruhan Malang, 2024)
Elementary school students' skills in mastering mathematics (numeracy literacy) still need to be higher; most are below the minimum ability standard. This research aims to determine the ability of fifth-grade elementary school students to understand fractions completely through a realistic mathematics learning approach. The research method used utilizes Kurt Lewin's classroom action research. The research results illustrate that a realistic mathematics learning approach can increase the strengthening of mathematical skills simultaneously, especially in mastering the skills of understanding fractions. Thus, realistic mathematics learning is an innovative and effective way to strengthen students' abilities in mathematics subjects. Teachers are asked to systematically and massively utilize this approach in their learning practices for the following purposes.